Corporate Rebranding: An Integrative Review of Major Enablers and Barriers to the Rebranding Process. (5th July 2013) - Miller, Dale; Merrilees, Bill; Yakimova, Raisa
<x xml:space="preserve">Abstract</x> In the field of corporate rebranding, which is an emerging area of research, the literature consists largely of descriptive case studies that are scattered across diverse contexts. These studies take divergent theoretical perspectives that often inform only aspects of rebranding, leaving researchers and managers without a comprehensive understanding of the corporate rebranding process. In adopting a holistic theory of corporate rebranding to organize a review of the literature, this study aims to present an integrated review of the major enablers and barriers to corporate rebranding, with special attention to contextual factors. Through an examination of 76 cases in 61 articles, the paper contributes a new general model of corporate rebranding. Unlike previous models of corporate rebranding, the new model incorporates both single‐ and multi‐phase enablers and barriers. Critical to successful corporate rebranding are the identification and application of six major enablers, including strong rebranding leadership and coordination among multiple functions and stakeholder groups. The new model suggests directions for future research, and the paper discusses how managers can use the model to inform rebranding practice and improve corporate rebranding outcomes.